2009
DOI: 10.1002/cmr.b.20144
|View full text |Cite
|
Sign up to set email alerts
|

Development of a QA phantom and protocol for proton magnetic resonance spectroscopy

Abstract: ABSTRACT:The purpose of this study was to develop a special proton magnetic resonance spectroscopy (1H-MRS) phantom, to establish and verify a quality assurance (QA) protocol, and to perform QA for a MR system. For a complete QA protocol, seven principal quality factors (PQFs) were measured. For evaluation of localization and quantification accuracy, two PQFs which are difficult to measure in commercial phantoms, we developed the layered dumbbell-shaped phantom. The performance sensitivity of our phantom was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…However, the signal intensity test performed for 1.5 T was not done for 3.0 T because of susceptibility effects caused by air bubbles A c c e p t e d M a n u s c r i p t in the phantom (Rice et al, 1998;Woo et al, 2009). This indicates that the changes in VOI positioning and the location in the phantom are sensitive to signal intensity with magnetic field strength and pixel size.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…However, the signal intensity test performed for 1.5 T was not done for 3.0 T because of susceptibility effects caused by air bubbles A c c e p t e d M a n u s c r i p t in the phantom (Rice et al, 1998;Woo et al, 2009). This indicates that the changes in VOI positioning and the location in the phantom are sensitive to signal intensity with magnetic field strength and pixel size.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, the inserted container contents can evaporate and become severely distorted with artifacts that occur from air within the container. This QA test was performed across a series of periods, and the SNR values of NAA in the brain-mimicking solution had an interval between 40 and 50 (SNR in 1.5 T instrument, 20-30) (Woo et al, 2009). Thus, compared to with the concentration and signal intensity of metabolites of the human brain, the results were reasonable (Barker et al, 2001;Wellard et al, 2005).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…It is also possible that some change‐points (for example around October 30, 2007) were influenced to some degree by service engineers' interventions. However, precise correlation of the changes observed in our in vitro spectroscopic measurements with the actual changes in hardware performance would require more elaborated and time‐consuming quality control procedures performed in parallel with the presented ones (28) . Although service engineers usually check the performance of MRI systems during the routine visits, Sobol et al (29) found that 80% of the independently evaluated systems revealed deficiencies affecting image quality.…”
Section: Discussionmentioning
confidence: 98%